Ethical Dilemmas in Visual Anthropology and Sociology in the Era of Artificial Intelligence - Khattri, Man Bahadur; Pandey, Rishikesh; Roy, Ratan Kumar; Subedi, Madhusudan; van Teijlingen, Edwin; Parker, Sara; Bhandari, Prem (Dhaulagiri Journal of Sociology and Anthropology, 2025)
Scholars worldwide are in dialogue about using Artificial Intelligence (AI) in various fields of research. It has supported enhancing work efficiency, including social science research. Although ethical use of AI is still fuzzy, the use of AI in visual anthropological and sociological research that entails the Interpretive Approach raises several questions. This editorial highlights three key questions: Are researchers satisfied with the interpretation (the meaning created) by AI, i.e., the authenticity of the interpretation? Can AI reach the depth of the details of the visual object being interpreted? Thirdly, what ethical issues would AI-based research encounter if AI were highly supportive? Answering these questions, however, is not easy. Since a detailed analysis of these components needs rigorous research work, we consider issues that will be the basis for further research in this editorial note. Hence, the purpose of this note is to bring the research agenda to the forefront of researchers for further investigation rather than answering specific research questions mentioned here.